Effect of emulsion fuel on engine emissions-A review - Hasannuddin, A. K. (Springer Verlag, 2016)
Emulsion fuel is an unconventional fuel for diesel engines, which can be used without modifications in the engine. The benefits of an emulsion fuel include lowering the emissions of nitrogen oxides (NO x ) and particulate matter (PM) which are harmful to health and cause diesel engines to suffer. This paper explains in detail the effect of water in the emulsion fuel on the emissions of NO x, PM, carbon monoxide (CO), hydrocarbon (HC), smoke and exhaust temperature. Experimental results from various researchers show a decrease in the NO x and PM emissions simultaneously. However, the results with the increasing water percentage in emulsion fuel are not consistent for HC and CO emissions. The water content in emulsion fuel affects the combustion and reduces the peak temperature in the combustion chamber. On the other hand, microexplosion phenomenon occurs and causes an increase in the volatility of diesel fuel which improves the combustion efficiency.